A Single-Center Review of Radiologically Diagnosed Maxillofacial Fractures: Etiology and Distribution. Issue 1 (February 2017) - Halsey, Jordan N.; Hoppe, Ian C.; Granick, Mark S.; Lee, Edward S.
The etiology of fractures of the maxillofacial skeleton varies among studies, with motor vehicle accidents and assaults oftentimes the most common. The number of males outnumbers females throughout most studies. Fractures of the zygoma, orbit, and mandible are usually cited as most common fracture types. This study examines a single center's experience with regards to etiology and distribution of fractures. A retrospective review of all radiologically confirmed facial fractures in a level 1 trauma center in an urban environment was performed for the years 2000 to 2012. Patient demographics, etiology of injury, and location of fractures were collected. During this time period, 2, 998 patients were identified as having sustained a fracture of the facial skeleton. The average age was 36.9 years, with a strong male predominance (81.5%). The most common etiologies of injury were assault (44.9%) and motor vehicle accidents (14.9%). Throughout the study period, the number of fractures as a result of assault remained relatively constant, whereas the number as a result of motor vehicle accidents decreased slightly. The most common fracture observed was of the orbit, followed by mandible, nasal bones, zygoma, and frontal sinus. Patients sustaining a fracture as a result of assault were more likely to have a mandible fracture. Patients in motor vehicle accidents were more likely to suffer fractures of the maxilla, orbit, and frontal sinus. Mandible fractures are more common in cases of assault. Motor vehicle accidents convey a large force, which, when directed at the craniofacial skeleton, can cause a variety of fracture patterns. The decreasing number of fractures as a result of motor vehicle accidents may represent improved safety devices such as airbags.